Typing of isolates of Clostridium perfringens from healthy and diseased sheep by multiplex PCR - Kalender, Hakan; Ertas, H.B.; Cetinkaya, B.; Muz, A.; Arslan, N.; Kilic, A. (Czech Academy of Agricultural Sciences, 2005)
In this study, C. perfringens strains isolated from healthy and diseased sheep were analysed by multiplex PCR in order to to detect the presence of the alpha, beta, epsilon, iota and enterotoxin genes. C. perfringens was isolated from 52 of 104 sheep with enterotoxemia signs and from 61 of 194 clinically healthy sheep. Genotyping of 52 strains from diseased sheep indicated that 33 (64%) were type A, 11 (21%) type D and 8 (15%) type C. Of 61 strains from healthy sheep, 58 (95%) were type A and 3 (5%) type D. The other types of C. perfringens were not detected, and none of the isolates contained the enterotoxin gene. This result indicates that the enterotoxin of C. perfringens does not play the important role in the occurence of enterotoxemia in sheep. © 2008 Veterinarni Medicina.
Keywords: C. perfringens; PCR; Sheep; Toxin genes